No evidence for an elephant-termite feedback loop in Sand Forest, South Africa. (November 2016) - Lagendijk, D.D.G.; Davies, A.B.; Eggleton, P.; Slotow, R.
Abstract: Termites and mammalian herbivores might derive mutual benefit from each other through positive feedback loops, but empirical evidence is lacking. One suggested positive feedback loop is between termites and elephant, both ecosystem engineers. Termites, as decomposer organisms, contribute to nutrient cycling and soil enrichment, creating hotspots with increased forage quality. Elephant are known to select these high quality vegetation patches, depositing woody debris when foraging, but it is unknown whether elephant presence might affect termites, and if a feedback loop between these two taxa exists. We tested this hypothesis by measuring termite diversity and activity over three months in the summer wet season, inside and outside a long-term (eight years) elephant exclosure experiment in Sand Forest at Phinda Private Game Reserve, South Africa. Termites were sampled using cellulose baits and woody debris was quantified using line transects. Termite activity was not affected by eight years of elephant absence, despite a greater volume of woody debris where elephant were present. Termite assemblages were similarly unaffected by elephant absence. Apart from Schedorhinotermes, all other termite genera were sampled in both treatments. Therefore, the postulated positive feedback loop between termites and elephant is not supported in Sand Forest. However, this does not contradict findings that areas with high termite activity positively influence herbivore foraging, only that elephant foraging does not affect termite activity. This suggests that elephant disturbance (and elephant management policies) has little to no effect on termites and the fundamental roles they play in ecosystems over at least the short-term. Highlights: A positive feedback loop between elephant and termites is suggested but untested. Termite generic densities, abundances and assemblages were not affected by elephant. Activity levels (frequency and intensity of attack) were not affected by elephant. This despite higher dead wood availability where elephant were present. Elephant management policies have no effect on termite presence and activity levels.